A construction strategy for a baculovirus‐silkworm multigene expression system and its application for coexpression of type I and type II interferons. Issue 3 (19th December 2019) - Liu, Xingjian; Yang, Xin; Mehboob, Arslan; Hu, Xiaoyuan; Yi, Yongzhu; Li, Yinü; Zhang, Zhifang
Abstract: The Bombyx mori nucleopolyhedrovirus ( Bm NPV) baculovirus expression system (BES) is a eukaryotic expression system. It possesses great capability for post‐translation modification in expression of foreign proteins. With the counterselection cassette rpsL‐neo and phage λ‐Red recombinase, the defective‐rescue Bm NPV BES reBmBac can be employed for efficient heterologous multigene coexpression at different gene sites in one baculovirus genome. In the present study, a recombinant baculovirus, reBm‐Cαγ, carrying two types of chicken interferon (IFN) genes ( chIFN‐α and chIFN‐γ ) was constructed using the reBmBac system. The chIFN‐α and chIFN‐γ genes were inserted into the same baculovirus genome at the polyhedron and p10 gene sites, respectively. The recombinant baculovirus was capable of coexpressing both chIFN‐α and chIFN‐γ. The expression levels of the two types of IFN in the coexpression product were exponentially high, at approximately 1.7 and 2.5 times higher, respectively, than those in the corresponding single‐expression products. The increase in expression level corresponds to replacement of the nonessential p10 gene in the reBm‐Cαγ recombinant baculovirus. This coexpression of recombinant chicken IFNs showed superior antiviral activity. Abstract : In this study, we developed a construction strategy of recombinant Bombyx mori nucleopolyhedrovirus for multigene coexpression. This strategy provides a method for gene deletion or insertion at any site of the baculovirus genome in Escherichia coli . Using this strategy, we constructed the recombinant baculovirus containing two types of chicken interferon genes (interferon‐α and interferon‐γ) at different gene sites. The production of silkworm infected with this recombinant baculovirus shown higher expression level and antiviral activity.